2021
DOI: 10.3390/nu13031033
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Short-Term “Fat Adaptation with Carbohydrate Restoration” Diet on Metabolic Responses and Exercise Performance in Well-Trained Runners

Abstract: Periodized carbohydrate availability can enhance exercise capacity, but the effects of short-term fat adaptation carbohydrate restoration (FACR) diets on metabolic responses and exercise performance in endurance athletes have not been conclusively determined. This study aimed to investigate the effect of a FACR diet on measures of resting metabolism, exercise metabolism, and exercise performance. Well-trained male runners (n = 8) completed a FACR dietary intervention (five days’ carbohydrate < 20% and fat &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
(62 reference statements)
1
5
0
1
Order By: Relevance
“…Consistent with our results, previous studies demonstrated that short and longer‐term HFD increases both EI and EE, with augmented fat oxidation and consequently reduced RER (Brown et al, 1985 ; Burke et al, 2021 ; Che et al, 2021 ; Gregory et al, 2011 ; Hansen et al, 2007 ; Helge et al, 2001 ; Sasaki et al, 2014 ). This is driven by increased utilization of intramuscular and plasma triglyceride/non‐esterified fatty acids stores (Helge et al, 2001 ; Howard & Margolis, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with our results, previous studies demonstrated that short and longer‐term HFD increases both EI and EE, with augmented fat oxidation and consequently reduced RER (Brown et al, 1985 ; Burke et al, 2021 ; Che et al, 2021 ; Gregory et al, 2011 ; Hansen et al, 2007 ; Helge et al, 2001 ; Sasaki et al, 2014 ). This is driven by increased utilization of intramuscular and plasma triglyceride/non‐esterified fatty acids stores (Helge et al, 2001 ; Howard & Margolis, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…This is driven by increased utilization of intramuscular and plasma triglyceride/nonesterified fatty acids stores (Helge et al, 2001;Howard & Margolis, 2020). These observations were confirmed in mouse models (Brown et al, 1985;Sasaki et al, 2014) as well as in human studies (Burke et al, 2021;Che et al, 2021;Gregory et al, 2011;Hansen et al, 2007;Helge et al, 2001). Yet, the wheel-omission-mediated fuel oxidation changes are beyond merely reflecting the diet, since both diets, though to different proportions, include both carbohydrates and fat, and it is the wheel omission that decreased fuel oxidation specifically of the minor nutritional source, which had been utilized under conditions of greater energy demand.…”
Section: Discussionmentioning
confidence: 73%
“…In contrast to the current investigation, most studies included a time trial to assess the endurance performance advantages following HFLC diets in combination with a carbohydrate restoration. According to data from these trials, time trial performance were similar in the high fat and high carbohydrate groups with a slightly higher power output high carbohydrate group during high-intensity phases [5,[31][32][33].…”
Section: Discussionmentioning
confidence: 92%
“…All subjects were instructed to keep daily food/beverage intake diaries by using a nutrient analysis application on their mobile phone (Boohee, Information Technology Co., Ltd., Shanghai, China) for the entire duration of the study. The use of Boohee app for quantifying food intake was previously shown to be an effective dietary monitoring tool [ 28 ]. During the pre-screen period, a 3-day food record was obtained using this application, including 2 weekdays and 1 weekend day, and was used to determine baseline energy substrate and caloric intake (% energy intake from carbohydrate, fat, and protein in each meal and snacks).…”
Section: Methodsmentioning
confidence: 99%